Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1063/1.2740472
|View full text |Cite
|
Sign up to set email alerts
|

Proposal and analysis of a silica fiber with large and thermodynamically stable second order nonlinearity

Abstract: Articles you may be interested inCopyright by the AIP Publishing. Xu, Yong; Wang, Anbo; Heflin, James R.; et al., "Proposal and analysis of a silica fiber with large and thermodynamically stable second order nonlinearity," Appl. Phys. Lett. 90, 211110 (2007); http:// dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…After combining Eqs. (4), (6), (9), and (10), we find Q NP (generated by NP absorption and scattering) to be…”
Section: Functional Microspheres Coated With Aumentioning
confidence: 77%
See 1 more Smart Citation
“…After combining Eqs. (4), (6), (9), and (10), we find Q NP (generated by NP absorption and scattering) to be…”
Section: Functional Microspheres Coated With Aumentioning
confidence: 77%
“…Despite these advantages, silica-based high Q resonators also face some intrinsic limits. For example, silica possesses neither second order nonlinearity [9] nor plasmonic resonances [10]. Consequently, it is difficult to investigate important processes such as second order parametric oscillation [11] or surface enhanced Raman scattering in such resonators [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Optical fibers are used in optical communication systems, sensing and biomedical applications [1,3]. However, their major limitation is the lack of nonlinear effects [4][5][6]. Silica possess third order nonlinearity such as four-wave-mixing, but lakes second order nonlinearity.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, investigation of nonlinear optics in silica-based materials focuses primarily on third order processes such as Kerr effects. In a recent Letter [2], we demonstrated that a silica fiber coated with radially aligned nonlinear molecules, despite its highly symmetric geometry, can exhibit large and thermodynamically stable second order nonlinearity. Both theoretically and experimentally, evidence that centrosymmetry does not preclude second order nonlinear response has been reported in the context of colloidal particles in bulk solution [3][4][5].…”
mentioning
confidence: 97%
“…Since the electric field of a TM WG mode is dominated by its radial component, we can define an effective mode volume as V eff R R R jE r j 2 dv=jE r j 2 max =2, where jE r j max is the maximum jE r j value. With this definition, we can estimate the pump energy stored in the microsphere as " 0 " r jEj 2 ave V eff =2, where jEj ave is the average electric field strength. From coupled mode analysis [10,16], the pump power traveling in the fiber taper is related to the pump energy stored within the microsphere, which gives P pump !…”
mentioning
confidence: 99%